2023
DOI: 10.3899/jrheum.220752
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complement in Autoimmune Disease-Associated Thrombotic Microangiopathy and the Potential for Therapeutics

Abstract: The complement system is a tightly regulated, cascading protein network representing a key component linking the innate and humoral immune systems. However, if misdirected or dysregulated, it can be similarly damaging to host-tissue. The role of complement dysregulation on vascular endothelial cells has been well established in atypical hemolytic uremic syndrome (aHUS), a thrombotic microangiopathy (TMA) characterized by microangiopathic hemolytic anemia, thrombocytopenia, and target organ injury. Yet a great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…It is clear that P-selectin has both pro-in ammatory and thrombogenic activities, having roles in immune cell in ltration, platelet aggregation and coagulation [29,30], all of which are relevant to GMH and injury progression. And while a 2.12Psel-Crry type construct is obviously not a therapeutic candidate for GMH or other hemorrhagic conditions, it is noteworthy that complement activation is closely associated with multiple thrombotic conditions; for example various rheumatic and autoimmune conditions, transplant related conditions and renal microangiopathies [40][41][42]. Also in this context, we have shown that complement inhibition potentiates thrombolytic therapy with tissue plasminogen activator in a model of ischemic stroke [43].…”
Section: Discussionmentioning
confidence: 83%
“…It is clear that P-selectin has both pro-in ammatory and thrombogenic activities, having roles in immune cell in ltration, platelet aggregation and coagulation [29,30], all of which are relevant to GMH and injury progression. And while a 2.12Psel-Crry type construct is obviously not a therapeutic candidate for GMH or other hemorrhagic conditions, it is noteworthy that complement activation is closely associated with multiple thrombotic conditions; for example various rheumatic and autoimmune conditions, transplant related conditions and renal microangiopathies [40][41][42]. Also in this context, we have shown that complement inhibition potentiates thrombolytic therapy with tissue plasminogen activator in a model of ischemic stroke [43].…”
Section: Discussionmentioning
confidence: 83%